1999
DOI: 10.1007/s002210050821
|View full text |Cite
|
Sign up to set email alerts
|

Impaired anticipatory finger grip-force adjustments in a case of cerebellar degeneration

Abstract: We describe adjustments in grip force as a consequence of fluctuations in inertial load force during vertical movements of the upper limb in a patient with cerebellar degeneration. Normally grip force is adapted to load-force fluctuations, in particular to the maximum load force, which occurs early in upward movements and late in downward movements. Increased grip force during movement was observed in the patient, but the timing of maximum grip force was not different between upward and downward movements. Thi… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

4
38
0
2

Year Published

2000
2000
2009
2009

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 73 publications
(44 citation statements)
references
References 16 publications
4
38
0
2
Order By: Relevance
“…The cerebellum is thought to be the area that enables the prediction of the consequences of our motor commands (Miall and Wolpert 1996;Miall et al 1993;. In support of this cerebellar role in prediction, cerebellar damage can lead to specific deficits in predictive grip force modulation (Babin-Ratte et al 1999;Muller and Dichgans 1994). Conditioning and anticipatory grip force may therefore share common neurophysiological mechanism.…”
Section: Discussionmentioning
confidence: 99%
“…The cerebellum is thought to be the area that enables the prediction of the consequences of our motor commands (Miall and Wolpert 1996;Miall et al 1993;. In support of this cerebellar role in prediction, cerebellar damage can lead to specific deficits in predictive grip force modulation (Babin-Ratte et al 1999;Muller and Dichgans 1994). Conditioning and anticipatory grip force may therefore share common neurophysiological mechanism.…”
Section: Discussionmentioning
confidence: 99%
“…Patients with a damaged cerebellum lack the tight coordination of grip and load force, often exerting more grip force than needed and having difficulties in timing motor actions e.g. to compensate for predictable perturbations (Babin-Ratté et al, 1999;Nowak et al, 2002;Serrien and Wiesendanger, 1999). Lesions in other areas involved in motor control such as the cerebral cortex or striatum result in paralysis or involuntary movement rather than a loss of coordination.…”
mentioning
confidence: 99%
“…The tight coupling between load (L) and grip (G) forces during voluntary movement of a hand-held object in vertical direction is well established [1][2][3][4][5]7,8]. It was also shown that the grip force is affected by physical properties of the object, such as the shape of object, texture of contact surface, as well as task properties, such as predictability or unpredictability [5,[9][10][11][12][13]. It is interesting to note that the grip force modulation in people is in sharp contrast to the grasp control realized in contemporary robotic hands where-to simplify the control-the grasp force is fixed during the performance [14].…”
Section: Introductionmentioning
confidence: 99%
“…Other studies also demonstrated that precision grip force control capacity became degraded with advancing age [10,15,16]. Patients with some neurological disorders also experience difficulties in precise adjustments of the grip force to the task demands [9,11,[17][18][19][20][21][22][23]. For instance, patients with cerebral stroke have deficits in sensory input and therefore demonstrated an exaggerated grip force compared to normal control [41].…”
Section: Introductionmentioning
confidence: 99%